Self‐assembled silicon nanocrystal arrays for photovoltaics. Issue 8 (4th February 2015) - Schnabel, M.; Weiss, C.; Löper, P.; Wilshaw, P. R.; Janz, S.
<x xml:space="preserve">Abstract</x> Silicon nanocrystals (Si NCs) are a promising candidate for the top cell of Si tandem solar cells since their bandgap exceeds that of bulk silicon and can be tuned by adjusting nanocrystal size. Due to this effect, size control is required to maintain a uniform bandgap throughout a Si NC film. This can be achieved by annealing superlattices of Si‐rich and stoichiometric dielectrics. This paper reviews the progress that has been made using host matrices SiO2, Si3N4, and SiC. Si NCs in SiO2 show excellent NC size and shape control and strong quantum‐confinement‐related photoluminescence, however electrical conductivity is poor. Ordering and size control is also obtained in Si3N4, but conclusive evidence of quantum confinement is lacking. Preparing ordered but separated Si NCs in SiC is difficult, but the narrow parameter space in which this is possible has been elucidated, good electrical conductivity was obtained, and functioning single‐junction and tandem cells have been produced. Si NC formation can now be well‐controlled in all three materials, and the key weaknesses for photovoltaics have been identified to be the electrical conductivity of SiO2, and defect density for Si3N4 and SiC. Addressing these is expected to lead to competitive Si tandem solar cells.